Africa’s progress toward meeting current nutrition targets - Haddad, Lawrence James; Ag Bendech, Mohamed; Bhatia, Komal; Eriksen, Kamilla; Jallow, Isatou; Ledlie, Natasha (International Food Policy Research Institute, 2016)
In the era of the Sustainable Development Goals, the world faces many seemingly intractable problems. Malnutrition should not be one of them. The incentives to improve nutrition are strong, and determined countries can make rapid advances in malnutrition reduction. Good nutrition provides a vital foundation for human development that is central to meeting our full potential. When nutrition status improves, a host of positive outcomes can follow for individuals and families. Improved nutrition in Africa means many more children will live past the age of five, their growth will be less disrupted, and they will gain in height and weight. Their cognitive abilities will develop more fully, allowing them to learn more both in and outside of school. As a result of sufficient nourishment and a positive early environment, children are more likely to get better jobs and suffer fewer illnesses as adults—aging healthily and living longer to support the African Union Agenda 2063 vision of a prosperous and united Africa (AU 2015b).